Learning Design of Sphere using Realistic Mathematics Education Assisted by Interactive Video - Nursyahidah, Farida; Albab, Irkham Ulil; Rubowo, Maya Rini (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
Numerous studies, particularly in sphere material, have highlighted students' challenges in grasping the notion of geometry. Typically, the teacher only teaches the subject using the formula, omitting the notion altogether. Moreover, this study intends to create a hypothetical learning trajectory for the sphere material by incorporating the Syawalan tradition from Pekalongan into the learning process through the Indonesian Realistic Mathematics Education approach, or PMRI. The methodology employed is design research, divided into three stages: preliminary design, design experiment, and retrospective analysis. As a result, this study focuses exclusively on the outcomes of the design experiment process, namely the pilot experiment. Video recordings, photographs, observations, deep interviews, documentation, field memos, and student activity sheets were all used to collect and analyze data to improve HLT. The outcome of this study is a hypothetical learning trajectory for sphere material in the context of the Syawalan tradition. The student learning sequence comprises four series, which include observing an interactive video of the syawalan tradition context to characterize sphere elements, utilizing orange fruit to find the sphere's surface area, discovering the sphere's volume through the cylinder and magic seeds, and resolving sphere-related contextual problems. Additionally, the activities devised in this study can potentially develop students' interest and conception of sphere material in the ninth grade. DOI: https://doi.org/10.22342/jpm.17.3.20040.297-312